Pengaruh Kepuasan, Beban Kerja, dan Disiplin Terhadap Kinerja Karyawan PT Global Citra Pratama Batam - Jerico Jerico; Tiurniari Purba (eCo-Buss, 2024)
This study aims to analyze the effect of satisfaction, workload, and discipline on employee performance at PT Global Citra Pratama Batam. This type of descriptive research with a quantitative approach will be used in this study. The population is a permanent employee of PT Citra Global Pratama Batam totaling 122 people with the withdrawal of saturated sampling technique. Regression analysis is used to examine the relationship between these variables by testing data quality tests, classical assumption tests, influence tests and hypothesis testing. The findings of multiple linear regression analysis revealed that satisfaction can increase employee performance by 28.8%. Workload can increase employee performance by 31.3%. Discipline can increase employee performance by 45.4%. In the analysis of the coefficient of determination (R2) reveals that satisfaction, workload and discipline can simultaneously provide an explanation for employee performance with a magnitude of 61.0%. The findings of hypothesis testing have shown that satisfaction, workload and discipline have a positive and significant effect partially and simultaneously on employee performance at PT Global Citra Pratama Batam.